Effects of grain thickness on yield and quality of rice varieties in Jilin province - HE,Bing (2022)
Abstract The correlation between the grain thickness and the yield and quality of brown rice was studied using 9 japonica rice varieties harvested in Jilin Province in 2019. The results showed that there were significant differences between the grain thickness of different varieties. The grading of different grain thickness had a great influence on the grains per panicle and the seed setting rate in the yield components. Further, there was no significant correlation between grain thickness and grain type (aspect ratio), while a strong and significant negative correlation was identified between grain-thickness grading (< 2.0 mm) and processing quality. In addition, grain thickness was found to have a positive effect on the quality of taste. In conclusion, grain length, width, and thickness are independent genetic traits. The ratio of thicker grain-thickness-grading would increase with an improvement in the yield and processing quality, and an increase in the thinner grain-thickness-grading ratio would lead to degradation with regard to appearance and taste. The grain thickness of brown rice has an important impact on the quality of the rice.